A case study about the forest fire occurred on 05 July 2021 over Khenchela province, Algeria, using space-borne remote sensing - Guehaz, Riad; Sivakumar, Venkataraman (Frontiers in Remote Sensing, 2023)
Thank you for giving us the opportunity to submit a revised draft of my manuscript titled A case study about the forest fire occurred on 05 July 2021 over Khenchela province, Algeria, using space-borne remote sensing. We appreciate the time and effort that you and the reviewers have dedicated to providing your valuable feedback on my manuscript.We are grateful to the reviewers for their insightful comments on my paper. We have been able to incorporate changes to reflect most of the suggestions provided by the reviewers. The changes made are easily noticeable using track changes version of the attached manuscript.We hereby submit both manuscripts (i) with the track changes and (2) the clean manuscript (3) Figures and ( 4) Tables. We have also attached the replies to both reviewers.We look forward to hear a positive response.Riad Guehaz & Sivakumar Venkataraman.